Efektifitas Penggunaan Video Berbasis Budaya untuk Meningkatkan Literasi Matematika dan Karakter Siswa SMP - Dewi, Ratna Kumala; Hartati, Sulis Janu; Setiawan, Windi (Universitas Nahdlatul Ulama Pasuruan, 2022)
This study entitled Effectiveness of Using Video Learning Media to Improve Mathematical Literacy in Bethel Christian Middle School Surabaya. This study aims to describe and analyze culture-based videos in improving mathematical literacy on square, triangleand quadrilateral material at Bhetel Christian Junior High School Surabaya in the 2021/2022 even semester. The method used is the research method used in this study is a Pre-Experimental Design using the One-group Pretest-Postet design form. In this design there is a pretest before being given treatment and a posttest after being given treatment. Data analysis itself uses normality test, paired sample t-test, Wilcoxon test, N-Gain test. From the results of the Wilcoxon test that has been carried out, it can be seen that the significance value is 0.001 so there is a difference in the average results of the pretest and posttest of the two samples of mathematical literacy and critical thinking of junior high school students. It can be concluded that the results of mathematical literacy and critical thinking of junior high school students towards culture-based videos can increase. From the results of the N-Gain test that has been carried out, which occupies a playing score of 0.4488, which means that culture-based videos are quite effective in improving mathematical literacy and critical thinking of junior high school students.